Pengaruh Motivasi, Disiplin Kerja, dan Lingkungan Kerja Terhadap Prestasi Kerja Karyawan PT. Bank Muamalat Indonesia, Tbk Cabang Malang - Fitria Nur Azizah; Eka Afnan Troena (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Abstract: This research was conducted at PT. Bank Muamalat Indonesia, Tbk Branch Malang. The design of the research is explanatory research, and use quantitative research using multiple linear regression statistical tools. Result of this research showed that Motivation, Work Discipline, and Work Environment simultaneously or jointly significant effect on the Job Performance by Test F = 13.714 (Sig. 0,000). Partially, motivated significant effect on job performance with sig. 0.000 (t = 6.224). Keywords: motivation work discipline, work environment, job performance, PT. Bank Muamalat Indonesia, Tbk Branch Malang